Beach bummer - Higgins, Ryan T. (Higgins, Ryan T. Little Bruce book., 2024)
It's beach day in Soggy Hollow! Everyone is enjoying fun in the sun -- everyone, that is, except for Bruce. It's too hot, too sandy, and too windy! Bruce's favorite thing about summer? Doing nothing. In the shade. Where it's cool. Bruce's second favorite thing about summer? When it turns to fall.